2017
DOI: 10.1016/j.canlet.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Resistin potentiates chemoresistance and stemness of breast cancer cells: Implications for racially disparate therapeutic outcomes

Abstract: Breast cancer (BC) continues to be the most frequently diagnosed cancer in American women, which disproportionately affects women of African-American (AA) descent. Previously, we reported greater serum levels of resistin in AA BC patients relative to Caucasian-American (CA) patients, and established its role in growth and aggressiveness of breast tumor cells. Here we have investigated the role of resistin in BC-chemoresistance. MDA-MB-231 and MDA-MB-468 BC cells of CA and AA origin, respectively, were incubate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 62 publications
(75 reference statements)
4
36
0
1
Order By: Relevance
“…13 We and others have shown that certain AhR ligands induce apoptosis in TNBC cells. 40,41 In this study, we observed that silencing CYGB reduced 5F 203-mediated apoptosis, caspase-3/-7 activation, LMP, and cathepsin B release. 39 Many cancers, including breast cancer, support their survival by deregulating apoptosis induced by therapies, which makes it paramount to understand the mechanism(s) used to evade cell death.…”
Section: Discussionsupporting
confidence: 50%
“…13 We and others have shown that certain AhR ligands induce apoptosis in TNBC cells. 40,41 In this study, we observed that silencing CYGB reduced 5F 203-mediated apoptosis, caspase-3/-7 activation, LMP, and cathepsin B release. 39 Many cancers, including breast cancer, support their survival by deregulating apoptosis induced by therapies, which makes it paramount to understand the mechanism(s) used to evade cell death.…”
Section: Discussionsupporting
confidence: 50%
“…[38][39][40] It is well established that treatment of cancer cells with DOX induces apoptosis. 37,[41][42][43] We observed that all the tested Exo-DOX formulations outperformed free DOX in cytotoxicity toward PCCs. This could be due to the fact that drug efflux pumps actively pumpout DOX from the cancer cells.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, since we observed a trend of tumor progression and impaired therapeutic outcome in ob/ob mice (which lack functional leptin) as compared to their wild-type counterparts, obesity-associated factors (other than leptin) could also influence tumor progression and the impairment of chemotherapy. As serum level of resistin is very high in ob/ob mice, and we observed in vitro that resistin is equally partly responsible for causing impairment in the efficacy of DTIC, it is conceivable that even in the absence of leptin, resistin could be involved in impairing the efficacy of DTIC in ob/ob mice, as resistin is very well known to induce drug-resistant phenotype in various cancers [ 14 , 15 , 49 , 50 ]. Although, our in vitro results established the fact that both leptin and resistin are involved in impairing the response of melanoma cells to DTIC, it is difficult to validate their role in vivo due to lack of resistin knockout animals as well as resistin neutralizing antibody.…”
Section: Discussionmentioning
confidence: 99%